KONSEP KELEMBAGAAN MODAL VENTURA SEBAGAI LEMBAGA PEMBIAYAAN DI INDONESIA - Letri, Dilla Ayuna; Yulinda, Kiki; Tiara, Dora (Ensiklopedia of Journal, 2024)
Abstract: Financing institutions are one form of business in the field of non-bank financial institutions. The activities of this financing institution are carried out in the form of providing funds or capital goods without directly withdrawing funds from the public. One form of financing institution in Indonesia is Venture Capital. Venture capital is directed to help small businesses that are experiencing capital difficulties in their business activities or small businesses in the process of growing their business scale. The purpose of this study is to find out about the concept of venture capital as a financing institution in Indonesia. The approach method used is the Juridical approach. The concept of venture capital is basically not the same as ordinary capital participation. Banks that carry out bad credit in other companies by converting it into equity participation are not venture capital, likewise ownership of a company's share capital through the capital market cannot be classified as a venture capital business. However, a bank that finances a company can use the concept of venture capital. Venture capital institutions in Indonesia currently still do not fully use the concept of pure venture capital as is done by venture capital companies abroad. The institutional structure of venture capital that exists at this time is not separated from the legal entity of the venture capital fund on the one hand with the management of venture capital on the other.Keywords: Concept, venture capital, financing institutions.